BIOSYNTHESIS OF GOLD NANOPARTICLES BY BIOSORPTION USING NEOSARTORYA UDAGAWAE: CHARACTERIZATION AND INVITRO EVALUATION - Lakshmi, V. Jhansi; Kannan, K. P. (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The present study was aimed to investigate gold nanoparticles synthesized by fungal isolate Neosartorya udagawae and determination of their stability in biofluids to probe their aptness in drug delivery applications. Methods: In this procedure, gold nanoparticles were prepared by biosynthesis using seven days old culture of Neosartorya udagawae and aqueous chloroauric acid. After the complete reaction, the fungal biomass was subjected to UV-Vis, XRD, FT-IR Spectrum analysis, TEM, Zeta potential, SEM and EDX analysis. Results: Intra/extracellular synthesis of gold nanoparticles was confirmed by a sharp peak at 526 nm in UV spectroscopy. SEM, TEM analysis demonstrates the spherical shape of AuNPs with an average diameter of 50 nm and XRD confirm the crystalline gold nanoparticles. FTIR analysis reveals the presence of the protein shell around the gold nanoparticles. The zeta potential value of AuNPs was-36mV which confirmed the stability of nanoparticles dispersion. Gold nanoparticles have shown high stability in biofluids of Bovine Serum Albumin and Phosphate Buffer Saline at pH-5, pH-7and pH-9 which mimic the human colonic biological environment. Conclusion: The fungal synthesis of AuNPs has been experimentally demonstrated and their stability in BSA, 10% NaCl and PBS at pH-7. This might be a promising option for drug delivery applications in carcinogenic colon disorders in human beings. Â 